Towards big data framework in government public open data (GPOD) for health - Muhamad Ibrahim, Najhan; Ahmad Azri, Nur Hidayah Ilham; Idris, Norbik Bashah (Elsevier, 2022)
Today, data is one of the most valuable assets on the planet. As a valuable resource, data may be used to develop a wide range of data applications, all of which are driven by creativity and innovation. In order to obtain information and provide services, data is also a critical component. In recent years, Big Data (BD) has become a popular topic in global discussion. Big Data is new technology and knowledge generation phenomenon, that record, capture and execute a significant amount of data for usage in a variety of domains such as research, education, business, investing, health, and so on. The proliferation of data inspired by new methods of data gatherings such as via social media, wireless sensors, and data from government agencies, makes Big Data management an ultimate challenge because of its properties, which include storage volume, variation in nature, access speed, and data quality veracity. This study includes a thorough evaluation of existing theories and practical approach to addressed the public sector open data issues in order to determine the determinants of GPOD development of big data. In past studies to investigate the revolution of government public open data for health, the framework was dominantly used over architecture, infrastructures, followed by theoretical and conceptual framework, according to the review. The study revealed that most of the existing frameworks are still lack consideration of the requirement for public open data in health. There are less number of previous research has sophisticated Big data framework in GPOD for health. There also is still a lack of investment and adoption of Big Data in the public sector. The findings will help academics empirically study the revealed requirement and provide decision-makers a better knowledge of how to leverage GPOD adoption in health by taking appropriate actions.